2018
DOI: 10.1155/2018/1498640
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Inner Ear Disease: Immune Biomarkers, Audiovestibular Aspects, and Therapeutic Modalities of Cogan’s Syndrome

Abstract: Cogan's syndrome (CS) is a rare autoimmune disorder characterized by audiovestibular dysfunction and ocular inflammation. Currently, there is no specific serum autoantibody used in the diagnostic workup of CS. Treatment is based on immunosuppressive agents, mainly corticosteroids as first-line choice. Recently, novel therapeutic modalities in CS have emerged. These include tumor necrosis factor-α inhibitors and other biologicals. Despite medical treatment, hearing loss may progress to irreversible bilateral pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 69 publications
0
26
0
1
Order By: Relevance
“…This study may give additional evidence for MSCs as the safest method in hearing loss. MSCs are considered as potent immunomodulators in various autoimmune inner ear diseases (27). In an autoimmune hearing loss murine model, human adipose-derived mesenchymal stem cells (h-ADSCs), h-ADSCs down-regulate Th1-mediated autoreactive response that recruits antigen-specific Treg cells to secrete interleukin-10 and suppresses the self-reactive T-cells and protects cochlear hair cell loss from degeneration (28).…”
Section: Mesenchymal Stem Cells In Inner Hair Cell Regenerationmentioning
confidence: 99%
“…This study may give additional evidence for MSCs as the safest method in hearing loss. MSCs are considered as potent immunomodulators in various autoimmune inner ear diseases (27). In an autoimmune hearing loss murine model, human adipose-derived mesenchymal stem cells (h-ADSCs), h-ADSCs down-regulate Th1-mediated autoreactive response that recruits antigen-specific Treg cells to secrete interleukin-10 and suppresses the self-reactive T-cells and protects cochlear hair cell loss from degeneration (28).…”
Section: Mesenchymal Stem Cells In Inner Hair Cell Regenerationmentioning
confidence: 99%
“…Other than these inner ear-specific autoantibodies, the presence of tissue non-specific autoantibodies such as anti-nuclear antibody (ANA), anti-neutrophil cytoplasmic antibody (against myeloperoxidase (c-ANCA) and proteinase-3 (p-ANCA)), anti-endothelial cell antibody (AECA), anti-phospholipid/anti-cardiolipin antibodies, anti-thyroid antibodies, Rheumatoid factor and HSP-70 antibodies are proposed as diagnostic markers. [25][26][27]…”
Section: Immune Responses and Mechanism Of Isnhlmentioning
confidence: 99%
“…[52,53] Immuno-modulatory human adipose-derived mesenchymal stem cells (hAdMSC) have shown promising efficacy in treating immune-mediated manifestations in animal models; A study indicated an improvement of hearing in one patient. [27] Autologous AdMSCs have been suggested as a safe and efficient option for treatment of various autoimmune diseases and complications including ISNHL. [54] Regeneration of hair cells and gene therapy have been studied as potential therapeutic strategies for hearing loss.…”
Section: Genetic Susceptibility To Isnhlmentioning
confidence: 99%
“…Cogan’s syndrome (CS) is a very rare chronic autoimmune disease characterized by ocular inflammation and audiovestibular symptoms including tinnitus, vertigo and hearing loss ( 1 ). It mainly affects young adults without gender predominance ( 2 ). Standard treatment consists of systemic glucocorticoids that may be combined with glucocorticoid-sparing agents like methotrexate, azathioprine, cyclosporine, cyclophosphamide or tumor necrosis factor-α (TNF-α) inhibitors ( 2 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…It mainly affects young adults without gender predominance ( 2 ). Standard treatment consists of systemic glucocorticoids that may be combined with glucocorticoid-sparing agents like methotrexate, azathioprine, cyclosporine, cyclophosphamide or tumor necrosis factor-α (TNF-α) inhibitors ( 2 4 ). Management of inflammatory diseases in general is particularly challenging in female patients of reproductive age.…”
Section: Introductionmentioning
confidence: 99%